A Convenient One‐Pot Route to Screw‐Shaped [5]Azahelicenes via Rhodium(III)‐Catalyzed Multiple C−H Bond Activation. Issue 4 (23rd January 2017) - Li, Shuai‐Shuai; Liu, Chen‐Fei; Zhang, Guo‐Tai; Xia, Ying‐Qi; Li, Wei‐Huan; Dong, Lin
Abstract: A convenient rhodium(III)‐catalyzed cascade reaction of 7‐azaindoles and alkynes through multiple C−H bond activation for the synthesis of unique [5]azahelicenes has been developed. The optical property of these screw‐shaped helicene derivatives could be further utilized in electronic devices to recognize mercury ions. Abstract : Helically unique ! A convenient rhodium(III)‐catalyzed cascade reaction of 7‐azaindoles and alkynes through multiple C−H bond activation for the synthesis of unique [5]azahelicenes has been developed. The optical property of these screw‐shaped helicene derivatives could be further utilized in electronic devices to recognize mercury ions.